Mechanical and thermal properties of chitosan-filled polypropylene composites: The effect of acrylic acid - Salmah, Husseinsyah, Prof. Madya; Faisal, Amri; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Hanafi, Ismail (Society of Plastics Engineers, 2011)
Link to publisher's homepage at http://www.4spe.org/